Captain John Smith : - Hoobler, Dorothy (John Wiley & Sons, 2006)
Captain John Smith tells the real story behind the swashbuckling character who founded the Jamestown colony, wrote the first book in English in America, and cheated death many times by a mere hairbreadth. Based on rich primary sources, including Smith's own writings and newly discovered material, this enlightening book explores Smith's early days, his forceful leadership at Jamestown that was so critical to its survival, and his efforts upon his return to England to continue settlements in America. This unique volume also reveals the truth behind Smith's relationship with Pocahontas, a tale that history has greatly distorted. Bringing to life heroic deeds and dramatic escapes as well as moments of great suffering and hardship, Captain John Smith serves as a great testament to this important historical figure.